Warming-induced destabilization of polar coastal rock cliffs and the role of thermokarst: A case study of Forkastningsfjellet on Svalbard - Dirk Kuhn; Reginald L. Hermanns; Michael Fuchs; Nick Schüßler; Jewgenij Torizin; Juditha Aga; Jacob Bendle; Trond Eiken; Dirk Balzer (Science of The Total Environment, 2025)

Project ‘‘Mass Movements in Germany’’ and its implications for nationwide landslide susceptibility assessment - Jewgenij Torizin; Michael Fuchs; Dirk Balzer; Dirk Kuhn; Stefan Glaser; Dominik Ehret; Johannes Wiedenmann; Peter Dommaschk; Stefan Henscheid; Roland Strauß (Bulletin of Engineering Geology and the Environment, 2024)
The paper presents the framework and discusses the outcomes of the "Mass Movements in Germany" project—a collaboration of five State Geological Surveys (SGSs) and the Federal Institute for Geosciences and Natural Resources (BGR) to conduct a feasibility study for a nationwide landslide susceptibility map in Germany using harmonized datasets. Therefore, distinct methods representing heuristic, physically-based, and data-driven approaches were employed. In 14 consecutive modeling cases, we investigated parameter selection and preparation, model building, evaluation, and transferability issues. The results show that nationally harmonized datasets, deemed high-quality, exhibited data generalization at regional scales, affecting the reliability of the landslide susceptibility patterns. While using regional datasets on larger scales mitigated some generalization effects, heterogeneities in inventory datasets among distinct federal states pose challenges in creating a nationwide applicable model. Heterogeneous data require locally adjusted model designs affecting the model's transferability and comparability of data-driven models across large regions. Heuristic methods operate without observational data but require in-depth knowledge of the regional-geological conditions by involving expert groups rather than single experts. The physically-based model shows promising results with parametrization based on the pedotransfer functions and soil database supplementing the national soil map. However, this approach is limited to shallow translational landslides. Thus, considering all mass movement types, a single comprehensive approach for creating a nationwide landslide susceptibility map for Germany is currently not feasible. Close collaboration and further harmonization of datasets and methods involving all SGSs are needed.

Statistical landslide susceptibility assessment in a dynamic environment: A case study for Lanzhou City, Gansu Province, NW China - Jewgenij Torizin; Li-chao Wang; Michael Fuchs; Bin Tong; Dirk Balzer; Li-qin Wan; Dirk Kuhn; Ang Li; Liang Chen (Journal of Mountain Science, 2018)